Contrasting and Predicting Social Media’s Role in Addictive Use and Well-Being - Deniz Cemiloglu (17150980) (2025)
This paper explores the complex relationship between social media problematic use and their contribution to well-being. While social media platforms offer opportunities for connection, information access, and self-expression, concerns have arisen regarding their impact on mental health and in some cases their obsessive use leading to conflict with other life priorities. This study investigates the duality of social media’s effects, recognising that its impact on well-being can be both beneficial and harmful, depending on personal, psychological, and situational factors. Additionally, the paper examines whether problematic social media use (PSMU) correlates with perception of social media’s contribution to well-being (SM-WB) and explores common influencing factors and motivations. The data was collected via an online survey conducted among two distinct populations, the Arab (281, 141 females) and the UK (281, 155 females). We employed PERMA profiler to assess SM-WB whereas PSMU was measured through Social Media Disorder (SMD) scale. The results show that PSMU symptoms of preoccupation, tolerance, and withdrawal correlates positively with SM-WB in both Arab and UK samples. In a linear regression model, internal locus of control predicted SM-WB, whereas external locus of control and social media usage time predicted PSMU in both Arab and UK samples. Competence in using social media significantly predicted both PSMU and SM-WB in the Arab sample. These findings underscore the complexities of promoting healthier social media use and question the effectiveness of simply suggesting the reduction of usage as the sole solution, considering that usage can also enhance well-being. Other Information Published in: Journal of Technology in Behavioral Science License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s41347-025-00527-w